2004
DOI: 10.1159/000077318
|View full text |Cite
|
Sign up to set email alerts
|

Giant Fibrokeratoma of the Heel

Abstract: We describe a 77-year-old patient with a giant acquired fibrokeratoma on the heel. The size and the localization of the tumor was unusual. Simple shave excision was curative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 4 publications
1
26
0
1
Order By: Relevance
“…Exceptionally, there have been reported cases of giant acquired digital fibrokeratoma. Kakurai et al 4 and Bron et al 3 reported 3.2×3.8×1.5 cm and 3.0×1.5 cm acquired digital fibrokeratoma on the toe and heel as giant one respectively. In Korean dermatologic literatures, Cho et al 5 reported 1×1×3 cm giant acquired digital fibrokeratoma (Table 1).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Exceptionally, there have been reported cases of giant acquired digital fibrokeratoma. Kakurai et al 4 and Bron et al 3 reported 3.2×3.8×1.5 cm and 3.0×1.5 cm acquired digital fibrokeratoma on the toe and heel as giant one respectively. In Korean dermatologic literatures, Cho et al 5 reported 1×1×3 cm giant acquired digital fibrokeratoma (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…It is a benign tumor, almost always solitary, can be seen in adults and does not show spontaneous regression. In most cases, acquired digital fibrokeratoma appears as a small solitary nodules mainly on the fingers and toes, occasionally occurring on the lower lip, nose, elbow, pre-patellar area, nail bed and heel 3,[6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), but less commonly it may present as a symptomatic nodule much larger than 1 cm and can cause significant pain, also known as giant acquired digital fibrokeratoma . It most commonly occurs on the fingers but can also be seen on the palm, toes, and sole . Depending on the location of origin, the lesion can also be named acquired periungual fibrokeratoma (APF, Fig.…”
Section: Clinical Presentation and Epidemiologymentioning
confidence: 99%
“…Acquired digital fibrokeratoma (ADFK) is a rare but benign fibrous tumor that usually presents in middle‐aged adults as a solitary lesion with a collarette of slightly raised skin at the base . The most common locations are the fingers and toes near the interphalangeal joints, and the tumors generally measure <1 cm .…”
mentioning
confidence: 99%